The Impact of Banking Policies to the Macroprudential Policy - Kharohmayani, Desy; Wiryono, Sudarso Kaderi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
The interaction between banks and macroeconomics is of crucial importance to financial stability. This study aims to answer the question of how macroeconomic shocks are transmitted to banking variables or vice versa. The study investigated the impact of the banking policies, the principal component of analysis (PCA) of banking quality indicators (CAMEL), and BI's rate to the aggregate of GDP and GDP priority sectors. The methodology used is the Factor Augmented Vector Autoregressive (FAVAR) model to observe the endogeneity of the observed variables. The results show that there is substantial heterogeneity in the transmission of macroeconomic shocks, caused by CAR, CAMEL and BI rate. In the short run, we find that the impulse response functions of aggregate GDP and GDP per sector of priority to the shock of the CAR decrease and close to zero in the long term. Our findings align with the expected effects that the CAMEL has implications to the decline of GDP of priority sector. Finally, we find that the impulse response of aggregate GDP and GDP of the priority sector to monetary policy shock decreases in the short run and near to zero in the more extended period